Legal Aspects of Investment in Indonesia - Ahmad Fauzi (International Journal Reglement & Society (IJRS), 2022)
A logical consequence of a developing country seeing the importance of foreign capital and technology in accelerating economic growth, as well as Indonesia, but at the same time avoiding foreign domination of the Indonesian economy. An important factor needed in economic development is capital. One of the steps to overcome the need for capital, the Indonesian government has taken an approach in policy in the economic field, among others, by inviting foreign investment. Realizing that investment, both foreign and domestic, is a determining factor for the success of development in Indonesia. The role of law in development is to ensure that changes that occur by legislation and decisions of judicial bodies are better than irregular changes using mere violence. Economic development is in dire need of legal facilities and infrastructure so that they can actually achieve the goals in accordance with what was planned. Sunaryati Hartono further stated that law has a very important role to maintain balance and harmony and harmony between various interests in society.